(untitled) (Journal of Cancer Research Updates, 2021)
The ever-evolving field of nanotechnology has been applied over the years as an amazing potential tool in bone disorders through the development of targeted drug nanosystems. Bone diseases can be referred as any bone condition able to cause morbidity or even mortality to the host. Osteosarcoma has been most investigated condition for management and treatment by nanomedicine, and several nanomaterials such as nanoparticles, nanocapsules, nanospheres, nanodiamonds are being used for drug delivery. Likewise, other bone diseases, such as osteoporosis, osteonecrosis, osteoarthritis, bone tuberculosis have received nanotherapy with a large rate of success. The nanomedicine seems to make up a targeting lack by conventional therapy and chemotherapy, besides appointing to a trend of conservative clinical treatment, especially for severe disorders. Additionally, nanomedicine has advanced over the years, therefore, there is a strong need to accelerate its application in bone diseases reducing the mortality rate related to these conditions. This review article provides an overview on the advances of nanotechnology over the last two decades and highlights the pathways of investigations for targeted delivery nanoensembles.